Environmental contamination characteristics of heavy metals from abandoned lead–zinc mine tailings in China - Han, Wei; Zhao, Ruifeng; Liu, Wanrong; Wang, Yujing; Zhang, Shuai; Zhao, Kang; Nie, Jinglei (Frontiers in Earth Science, 2023)
China holds large scale lead-zinc mineral resources and the mining activities often cause severe heavy metals contamination. This research systemically assessed the contamination of eight heavy metals including Cu, Zn, Cd, Pb, Cr, Hg, Ni and As in mine tailing, soil and groundwater from 27 different contaminated sites across China. The results demonstrated that 1% of the mine mailing samples belong to hazardous waste and early 20% of mine tailing were identified as class Ⅱ non hazardous wastes as to the collected mine tailing samples. Regarding soils, Zn and Pb exhibit the highest value for the mean concentration of 5574.67 mg/kg and 2034.88 mg/kg, respectively. The index of geo-accumulation (Igeo) of eight heavy metals ranged from -3.62 to 7.67, while Zn, Pb and Cd exhibit the highest environmental risk level as the priority pollutants. The contamination level of these heavy metals in groundwater are generally in the order of Zn>As>Pb>Ni>Cd>Cu>Hg>Cr. 20% of the soils and 10% of the groundwater samples exceed the corresponding quality limits, respectively. The content of heavy metals in soil, groundwater and mine tailing are positively correlated, demonstrating the main pollution source and transport paths. The pollution level of the heavy metals in soil and groundwater are listed in the foreland and moderate position compared with similar sites from other countries, respectively. This work is helpful to master the pollution level of lead-zinc mining regions and direct the remediation activities of the target sites to support the environmental management of the abandoned mining and tailing waste in China.